Design and Development of a Digital Travel Authorization System Using Extreme Programming Method - Ersy Genius Nagari; Seftin Fitri Ana Wati; Reisa Permatasari (bit-Tech, 2025)
The process of submitting travel authorization letters at SMKN 6 Surabaya was previously carried out manually, leading to issues such as writing errors, miscalculations, and the lack of a digital archiving system. These problems highlighted the necessity for a digital solution to improve the efficiency and accuracy of the process. This study aims to design and develop a web-based travel authorization system using the Extreme Programming (XP) software development method. The XP methodology emphasizes close collaboration with users and rapid iterations throughout the development process. The system was designed with multi-role features, online approval, and digital archiving, enabling a full replacement of the manual process. Testing was conducted using Black-box Testing to verify that the system's functionality worked as expected. Additionally, User Acceptance Testing (UAT) was carried out to assess the design, usability, and efficiency from the user's perspective. The results from the UAT showed an average user satisfaction level of over 80%, indicating that the system was well-received by the users. This indicates that the system is effective in supporting the administrative process for travel authorization at SMKN 6 Surabaya. The implementation of this system is expected to enhance administrative efficiency, reduce human error, and streamline the management and digital archiving of travel documents. Furthermore, by automating the process, the system reduces the time and effort required for manual processing, ultimately improving the overall workflow within the institution.